From chisel to inscription: affordable protocols for the digital documentation of stone carving techniques. An experimental archaeology and traceological approach applied to epigraphy - Giulia Previti; Salma Kusumastuti; Beatrice Luci; Luca Malatesta; Cristina Lemorini (PLoS ONE, 2025)
This study investigates technological traces in stone epigraphs to reconstruct the methods, tools, and gestures used by artisans. It aims to analyze the techniques behind these inscriptions, highlighting skills, challenges, and interactions between craftspeople and stone, as well as territorial differences. Experimental archaeology enables the creation of a reference collection of replicated inscriptions, providing a comparative framework for technological trace analysis. By integrating experimental archaeology with traceological analysis, this research introduces a novel methodology for epigraphic studies through qualitative and quantitative approaches. A key contribution is the use of micro-photogrammetry as a non-invasive, non-destructive documentation technique, particularly valuable for fieldwork. This method enables high-resolution, meso-scale recording of inscriptions, even on immobile surfaces, common in epigraphic studies. Both qualitative and quantitative analyses are applied to interpret technological traces, including fatigue and abrasive wear. These traces reveal information on the direction, depth, and angle of engraving, shedding light on artisans’ techniques and challenges. Quantitative methods refine the analysis by providing precise insights into the engraved surface topography and roughness. Moreover, slope analysis clarifies tool orientation and movement, enabling the visualization of trace profiles and validating qualitative observations.